A review of the genus Miridiba Reitter (Coleoptera: Scarabaeidae: Melolonthinae) of Taiwan - Li, Chun-Lin; Yang, Ping-Shih; Wang, Chuan-Chan (Zootaxa, 2015)
The six Miridiba Reitter, 1902 species, including Miridiba taoi Li & Wang, new species, Miridiba huesiotoi Li & Yang, new species, and Miridiba taipei Wang & Li, new species from Taiwan are reviewed. A key for the identification of adults is provided. The following information is provided for each species: literature review, synonyms, diagnoses, data of material used, description or redescription, illustrations, distributional data, and remarks.